2001
DOI: 10.1016/s0924-9338(01)00568-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and clinical correlates of psychiatric co-morbidity in delusional disorder

Abstract: The present study investigated the occurrence and the clinical correlates of psychiatric co-morbidity in a sample of 64 patients with delusional disorder (DD). Subjects were evaluated with a semi-structured interview for the collection of demographic and clinical features of the disorder; co-morbid axis 1 disorders were determined according to the clinical interview using DSM-IV by Othmer and Othmer. Delusional disorder subjects with and without co-morbid diagnoses were compared to investigate whether the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
31
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 17 publications
16
31
0
3
Order By: Relevance
“…These results are consistent with previous studies carried out in the last decades 7,8 and those performed in patients with schizophrenia. 27,28 In agreement with the Halle Delusional Syndromes Study (HADES-Study), 11,12 we found no gender differences in the presence of depressive symptoms, depressive episodes, suicidal ideation, or suicide attempts during follow-up.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These results are consistent with previous studies carried out in the last decades 7,8 and those performed in patients with schizophrenia. 27,28 In agreement with the Halle Delusional Syndromes Study (HADES-Study), 11,12 we found no gender differences in the presence of depressive symptoms, depressive episodes, suicidal ideation, or suicide attempts during follow-up.…”
Section: Discussionsupporting
confidence: 94%
“…Maina et al found depressive comorbidity as an explanatory finding of an earlier age at onset of DD. 7 In previous studies, age at onset differed significantly according to the delusional theme. 9 For this reason, in the present study we included the presence of depressive comorbidity, DD type, and other psychosocial factors as covariates in the ANCOVA models.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Otros estudios han observado esta mayor proporción del TD en mujeres (3,5,(7)(8)(9)(10). Sin embargo, dicho hallazgo no es consistente con DSM-IV, ni con el estudio publicado recientemente por Wustmann y cols.…”
Section: Género Factores Demográficos Y De Riesgounclassified